2013
DOI: 10.1016/b978-0-12-404717-4.00006-8
|View full text |Cite
|
Sign up to set email alerts
|

The Yin and Yang of Protein Kinase C-theta (PKCθ)

Abstract: Protein kinase C-θ (PKCθ) is a PKC family member expressed predominantly in T lymphocytes, and extensive studies addressing its function have been conducted. PKCθ is the only T cell-expressed PKC that localizes selectively to the center of the immunological synapse (IS) following conventional T cell antigen stimulation, and this unique localization is essential for PKCθ-mediated downstream signaling. While playing a minor role in T cell development, early in vitro studies relying, among others, on the use of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 214 publications
(336 reference statements)
1
32
0
Order By: Relevance
“…Among these proteins were several with important immune functions (table S1). DMF-sensitive cysteine residues were found, for example, in multiple proteins that are either components or regulators of the NF-κB signaling pathway, including inhibitor of κB (IκB) kinase β (IKKβ or IKBKB) (24), protein kinase C-θ (PKCθ or PRKCQ) (25, 26), and tumor necrosis factor α–induced protein 3 (TNFAIP3, also known as A20) (27, 28) (table S1). Consistent with these, and potentially other, sites of DMF action being within the NF-κB pathway (19), we found that DMF blocked the nuclear translocation of p65 in anti-CD3/CD28–stimulated human T cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among these proteins were several with important immune functions (table S1). DMF-sensitive cysteine residues were found, for example, in multiple proteins that are either components or regulators of the NF-κB signaling pathway, including inhibitor of κB (IκB) kinase β (IKKβ or IKBKB) (24), protein kinase C-θ (PKCθ or PRKCQ) (25, 26), and tumor necrosis factor α–induced protein 3 (TNFAIP3, also known as A20) (27, 28) (table S1). Consistent with these, and potentially other, sites of DMF action being within the NF-κB pathway (19), we found that DMF blocked the nuclear translocation of p65 in anti-CD3/CD28–stimulated human T cells (fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that the WIP-WASP complex is associated with a Crk adaptor protein, which can interact with a TCRζ chain-bound activated ZAP-70 and thereby bring WIP into close physical proximity to the IS-residing PKCθ [24][25][26]. PKCθ was reported to physically associate with several other proteins, including 14-3-3τ , Cbl, Lck, Akt, moesin and PKC-interacting cousin of thioredoxin (PICOT) ( [9,10,27,28] and references therein), which may serve as substrates or upstream kinases of PKCθ, or regulators of its activity and/or subcellular distribution.…”
Section: The Role Of Pkcθ In T-cell Activation and Functionmentioning
confidence: 99%
“…The interest in PKCθ as a potential drug target has increased over time as it has become clear that it is essential for the induction of harmful inflammatory responses, including Th2-mediated allergies, Th17-mediated autoimmune diseases, graft compared with host disease and allograft rejection, but is dispensable for beneficial responses, including Th1-and cytotoxic T-lymphocyte (CTL)-mediated antiviral responses and graft compared with leukaemia response following bone marrow allotransplantation (reviewed in [10]). …”
Section: Pkcθ As a Drug Targetmentioning
confidence: 99%
See 2 more Smart Citations